The specific theory of systems a new paradigm - Pérez Durán, Gustavo de Jesús (Technium Social Sciences Journal, 2023)
The too general definition established by Bertalanffy L. (1968), has been used as the only system concept from 1968 to date and this led to the publication of many unscientific statements, which have never been verified with reality and which, nevertheless , continue to be accepted and used as a basis for reasoning and explanatory arguments from real situations. Here, a system definition is proposed that effectively replaces that of Bertalanffy and allows to explain in a logical, simple and practical way what systems are and opens the opportunity for new research and the rethinking of many concepts until now accepted in spite of its logical and methodological inconsistencies.